Longitudinal associations between perceived father and grandparent support of mothers in early childhood, and maternal mental health - Zhou, Xinru; Sun, Chang; Cai, Zhengjie; Li, Linhua; Wu, Yuju; Zhang, Hanwen; Raat, Hein; Medina, Alexis; Zhou, Huan (Frontiers in Psychiatry, 2025)
BackgroundMaternal mental health issues have emerged as a public health concern garnering increasing attention in recent years, especially in low and middle-income countries (LMICs). The involvement of fathers and grandparents in infant care has been recognized as a key factor affecting maternal mental health. However, few studies have focused on the relationship between infant care assistance patterns and maternal mental health issues. This study aims to examine how infant care assistance patterns and its transitions over time affect maternal mental health in rural China.MethodThis longitudinal study examined pregnant women in four rural Sichuan counties, China, using multi-stage random sampling to select 1054 mother-child dyads who completed baseline and follow-up assessments. We gathered four blocks of data: demographic characteristics, infant care assistance patterns (including sole maternal caregiving, joint parental caregiving, and maternal and grandparental caregiving), infant care assistance pattern transitions among mothers (including consistent assisted care, transitioned from sole mother care to assisted, transitioned from assisted care to sole mother, and sole mother care throughout) and maternal mental health issues (including depression, anxiety, and stress). Unordered multinomial logistic regression based on longitudinal data was used to explore the relationship between maternal mental health transitions and postnatal infant care assistance patterns transitions.ResultsOf the mothers, 9.61% reported having severe depressive tendencies, 10.06% had moderate to severe anxious tendencies, and 4.65% reported having moderate to severe stress tendencies. Unordered multinomial logistic regression revealed that compared to mothers with consistent assisted care, those who transitioned from assisted care to sole mother care during the first-year postpartum experienced deterioration or a lack of improvement in depression (RRR=1.83, p<0.05), anxiety (RRR=2.07, p<0.05), and stress (RRR=2.37, p<0.01). Besides, mothers without assisted care throughout were also at higher risk of deteriorating or not improving in anxiety (RRR=1.86, p<0.05) and stress (RRR=2.36, p<0.05).ConclusionThis study shows a link between infant care assistance patterns and maternal mental health. Mothers transitioning from assisted to sole care in the first postpartum year may face declining or stagnant psychological health, suggesting that family members offer support in infant care to share the caregiving responsibilities.